The importance of social science in the development of technology for complex public. (Revista Galega de Economía)
The importance of changing preexisting notions of the concept of inclusivity is something that has arised in recent times. Sociological perspectives on the way society is built show that specific misconceptions on what disabilities are consolidate the social distance of people that do not fit a normative idea of the body, especially when technology is designed with this prescriptive approach. The project VR4ALL is a normative revision which tries to adapt the design of VR technology to these concepts.